Niemiecko-Polska Szkoła Prawa (Wrocław-Berlin) - Malicka, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The German-Polish Law School is a joint project of the Faculty of Law, Administration and Economics of the University of Wrocław, the Faculty of Law of the Humboldt University of Berlin and the German-Polish Lawyers’ Association DPJV e.V. based in Berlin. In the academic year 2002/2003 the German Law School began operating at the Faculty of Law, Administration and Economics of the University of Wrocław. One year later the Polish Law School was established at the Faculty of Law of the Humboldt University of Berlin.The studies at the German-Polish Law School are supplementary. The programme lasts four semesters and concludes with obtaining the “German Law Certificate” in Wrocław, and the “Polish Law Certificate” in Berlin.The programme of studies encompasses the following subject-matters: public law, civil law, labour law, economic law, as well as commercial law and the law of commercial companies. The students in Wrocław take part in an intensive course of legal German language. Moreover, the students have an opportunity to undertake traineeship in Polish and German law firms, enterprises and public institutions.
Keywords: Niemiecko-Polska Szkoła Prawa Wrocław–Berlin; Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego; historia